Peran Pelayan Khusus (Penatua dan Diaken) Dalam Membangun Kesadaran Pemuda Beribadah di Jemaat GMIM Solafide Rasi Satu Wilayah Ratahan - Ohy, Thesalonika Dea Oprety; Komaling, Olga N.; Kalalo, Jefry (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
This article discusses the role of special servants, in this case elders and deacons, in building youth awareness of worship in the GMIM Solafide Rasi Satu congregation in the Ratahan region and this article also aims to examine how youth understand their duties and responsibilities in active worship. The problem faced is the lack of awareness of youth in congregational worship. This is also due to a lack of awareness of special servants, in this case elders and deacons, who pay attention to motivating young people to worship. This research uses qualitative research methods using procedures in the form of observation, interviews, data collection, data processing, data analysis and drawing conclusions. The implication of this research is that it can be useful for the development of practical theology in church services. This article is prepared by explaining what the role is, special servants, youth and worship as well as conclusions.